The effects of retinoic acid on endochondral ossification during prenatal development - Çolako?lu, Neriman; Aydin, Ayşe Murat; Özel, Hatice Banu; Ozan, Enver; Kükner, Aysel (My University, 2007)
Purpose: The aim of this study was to investigate the effects of excess all-trans retinoic acid on endochondral ossification in fetuses of rats. Material and Methods: Nine Wistar-Albino pregnant rats were used in this study. Pregnant rats were divided into three groups. The first group of rats were used as control. The second group were fed by gavage a single dose of 60 mg/kg all-trans retinoic acid on day 12 of gestation after neurulation which began 8.5 day of gestation and finished 11.5 day of gestation whereas third group received same dose all-trans retinoic acid on day 8 of gestation (before neurulation). All pregnant rats were sacrificed at day 18 of gestation. Six fetuses from each group were used. Ossification of fetal vertebrates was light microscopically and radiographycally determined. Results: Osteoblastic activity and ossified areas were significant in group-I. Ossification signs were not evident in group-III whereas ossification in vertebrates begun in group-II. However, ossified areas of group-II were less than those of group-I. Conclusion: In view of present findings, we suggest that administration of excess all-trans retinoic acid prior to neurulation disrupted bone morphogenesis. However, its administration following neurulation had less adverse effect on bone formation.
Retinoik asidin prenatal dönemdeki endokondral kemikleşme üzerine etkileri
Keywords: Bone; Fetus; Osteogenesis; Retinoic acid